Evolution of the primate trypanolytic factor APOL1 - Thomson, Russell (National Academy of Sciences, 2014)
ApolipoproteinL1 (APOL1) protects humans and some primates against several African trypanosomes. APOL1 genetic variants strongly associated with kidney disease in African Americans have additional trypanolytic activity against Trypanosoma brucei rhodesiense, the cause of acute African sleeping sickness. We combined genetic, physiological, and biochemical studies to explore coevolution between the APOL1 gene and trypanosomes. We analyzed the APOL1 sequence in modern and archaic humans and baboons along with geographic distribution in present day Africa to understand how the kidney risk variants evolved. Then, we tested Old World monkey, human, and engineered APOL1 variants for their ability to kill human infective trypanosomes in vivo to identify the molecular mechanism whereby human trypanolytic APOL1 variants evade T. brucei rhodesiense virulence factor serum resistance-associated protein (SRA). For one APOL1 kidney risk variant, a two-residue deletion of amino acids 388 and 389 causes a shift in a single lysine residue that mimics the Old World monkey sequence, which augments trypanolytic activity by preventing SRA binding. A second human APOL1 kidney risk allele, with an amino acid substitution that also restores sequence alignment with Old World monkeys, protected against T. brucei rhodesiense due in part to reduced SRA binding. Both APOL1 risk variants induced tissue injury in murine livers, the site of transgenic gene expression. Our study shows that both genetic variants of human APOL1 that protect against T. brucei rhodesiense have recapitulated molecular signatures found in Old World monkeys and raises the possibility that APOL1 variants have broader innate immune activity that extends beyond trypanosomes.